Effect of chromium on carbohydrate and lipid metabolism in a rat model of type 2 diabetes mellitus: the fat-fed, streptozotocin-treated rat - Şahin, Kazım; Onderci, Muhittin; Tuzcu, Mehmet; Ustundag, Bilal; Cikim, Gurkan; Ozercan, Ibrahim H.; Komorowski, James R. (W B Saunders Co-Elsevier Inc, 2007)
Chromium supplements are widely used as an alternative remedy for type 2 diabetes mellitus, (T2DM). In vitro study findings show that chromium picolinate (CrPic) may improve insulin sensitivity by enhancing intracellular insulin receptor. In this study, we evaluated the metabolic effects of CrPic in a rat model of T2DM. Male Sprague-Dawley rats (n = 45, 8 weeks old) were divided into 3 groups. The controls (group I) received a standard diet (12% of calories as fat); group II received a high-fat diet (HFD; 40% of calories as fat) for 2 weeks and then were intraperitoneally injected with streptozotocin (STZ, 40 mg/kg; HFD/STZ) on day 14; group III rats were given group II diets with the addition of 80 mu g CrPic per kilogram body weight per day. The addition of CrPic in the group III treatment lowered glucose by an average of 63% (P < .001), total cholesterol by 9.7% (P < .001), and triglycerides by 6.6% (P < .001) compared with group II treatment. Compared with group II, CrPic treatment also lowered free fatty acid levels by 24% (P < .001), blood urea by 33% (P < .05), and creatinine level by 25% (P < .01), and reduced the severity of glomerular sclerosis (P < .0001). Histopathologic findings suggest that the CrPic-treated group had normal renal tubular appearance compared with the HFD/STZ-treated group. Normal appearance of hepatocytes was observed in the CrPic-treated group. These results showed that CrPic has marked beneficial effects against microvascular complications. In conclusion, HFD/STZ rats provide a novel animal model for T2DM. Further treatment with CrPic for 10 weeks significantly ameliorated changes in metabolic risk factors including favorable changes in histopathology of the liver, kidney, and pancreas, suggesting its potential role in the management of diabetes. (C) 2007 Elsevier Inc. All rights reserved.
66th Annual Meeting of the American-Diabetes-Association -- JUN 09-13, 2006 -- Washington, DC
Keywords: Invivo Insulin Resistance; Dietary Chromium; Picolinate Supplementation; Laying Hens; Improves Carbohydrate; Egg-Production; in-Vivo; Glucose; Cholesterol; Sensitivity